2018
DOI: 10.4103/jfmpc.jfmpc_104_16
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose isotretinoin therapy and blood lipid abnormality: A case series with sixty patients

Abstract: Background:prolonged isotretinoin therapy for various skin diseases causes change in various parameters of lipid profile. Aim: to find out the effect of low dose isotretinoin on various parameters of lipid profile.Methods:A clinic based observational study with 60 patients of various skin diseases carried out in a skin outpatient department of a tertiary care hospital in eastern India. Patients were prescribed isotretinoin for relevant indications. Baseline lipid profile was checked and repeated after three mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“… 34 Furthermore, a very small number of patients (34) experienced hyperlipidemia while on isotretinoin treatment, which is much lower compared to other studies. 35 These low findings are attributed to most of our sample being young females (96%), and females generally are at lower risk of developing hypercholesterolemia. 36 Moreover, as shown in Table 7 , the lack of regular monitoring might have affected this finding.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“… 34 Furthermore, a very small number of patients (34) experienced hyperlipidemia while on isotretinoin treatment, which is much lower compared to other studies. 35 These low findings are attributed to most of our sample being young females (96%), and females generally are at lower risk of developing hypercholesterolemia. 36 Moreover, as shown in Table 7 , the lack of regular monitoring might have affected this finding.…”
Section: Discussionmentioning
confidence: 74%
“… 28 , 40 However conclusive evidence supports the claim that acne relapse is higher in males or females, specifically post isotretinoin therapy. 35 …”
Section: Discussionmentioning
confidence: 99%
“…ese recommendations were affirmed with a later study as the results were consistent with what has been found previously, that is, variable increase in several lipid profiles when a low-dose isotretinoin was administrated by the patients. is work also emphasized on continuous monitoring of lipid profile, especially in patient with risk factors of metabolic syndrome [37]. A recent study showed that a slight-to-modest increase of lipid and liver enzyme levels always occurs when isotretinoin is taken.…”
Section: Discussionmentioning
confidence: 99%
“…3.1 | Low-dose isotretinoin therapy and blood lipid abnormality Sarkar et al noted that among 60 patients on low-dose isotretinoin for relevant indications, hyperlipidemia was present in 25% of the patients only. Among the hyperlipidemia, hypertriglyceridemia was the commonest (Sarkar, Sarkar, & Patra, 2018). Administration of 1 g/day omega-3 may be hence plausible with its well-known efficacy in lowering hypertriglyceridemia (Mirnezami & Rahimi, 2018).…”
Section: Safety Of Low-dose Isotretinoinmentioning
confidence: 99%